Behaviour change interventions for the control and elimination of schistosomiasis: A systematic review of evidence from low- and middle-income countries. - Carlos A Torres-Vitolas; Suzan C M Trienekens; Willemijn Zaadnoordijk; Anouk N Gouvras (Public Library of Science (PLoS), 2023)
Background For the last two decades, schistosomiasis control efforts have focussed on preventive treatment. The disease, however, still affects over 200 million people worldwide. Behaviour change (BC) interventions can strengthen control by interrupting transmission through modifying exposure behaviour (water contact) or transmission practices (open urination/defaecation); or through fostering treatment seeking or acceptance. This review examines these interventions to assess their effectiveness in modifying risk practices and affecting epidemiological trends. Methodology/principal findings A systematic multi-database literature search (PROSPERO CRD42021252368) was conducted for peer-reviewed publications released at any time before June 2021 assessing BC interventions for schistosomiasis control in low- and middle-income countries. 2,593 unique abstracts were identified, 66 were assigned to full text review, and 32 met all inclusion criteria. A typology of intervention models was outlined according to their use of behaviour change techniques and overarching rationale: health education (HEIs), social-environmental (SEIs), physical-environmental (PEIs), and incentives-centred interventions (ICIs). Available evidence does not allow to identify which BC approach is most effective in controlling risk behaviour to prevent schistosomiasis transmission. HEIs' impacts were observed to be limited by structural considerations, like infrastructure underdevelopment, economic obligations, socio-cultural traditions, and the natural environment. SEIs may address those challenges through participatory planning and implementation activities, which enable social structures, like governance and norms, to support BC. Their effects, however, appear context-sensitive. The importance of infrastructure investments was highlighted by intervention models. To adequately support BC, however, they require users' inputs and complementary services. Whilst ICIs reported positive impacts on treatment uptake, there are cost-effectiveness and sustainability concerns. Evaluation studies yielded limited evidence of independent epidemiological impacts from BC, due to limited use of suitable indicators and comparators. There was indicative evidence, however, that BC projects could sustain gains through treatment campaigns. Conclusions/significance There is a need for integrated interventions combining information provision, community-based planning, and infrastructure investments to support BC for schistosomiasis control. Programmes should carefully assess local conditions before implementation and consider that long-term support is likely needed. Available evidence indicates that BC interventions may contribute towards schistosomiasis control when accompanied by treatment activities. Further methodologically robust evidence is needed to ascertain the direct epidemiological benefits of BC.